1991
DOI: 10.1016/0270-9139(91)90269-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of hepatic microcirculation in experimental rat cirrhosis: A scanning electron microscopic study

Abstract: Morphological changes of hepatic microcirculation, especially peribiliary plexus, in experimental rat cirrhosis that resulted from the repeated intraperitoneal injections of N-diethylnitrosamine, 100 mg/kg body weight/one shot/week, were examined by scanning electron microscope. Control rats were treated with saline. Whole blood vessels of the rats were perfused by saline and stuffed with methylmethacrylated resin. Multiple nodular changes were seen in the livers after the five injections (5 wk) of N-diethylni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…The arterial vascularization of the BD is characterized by abundant collateral vessels [23][24][25], and the PVP is an important factor in the function of the biliary epithelium [16]. CHA did not induce BDPF and decreased the number of PVPs in the adult CHA rats in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…The arterial vascularization of the BD is characterized by abundant collateral vessels [23][24][25], and the PVP is an important factor in the function of the biliary epithelium [16]. CHA did not induce BDPF and decreased the number of PVPs in the adult CHA rats in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…A recent scanning electron microscopic study has demonstrated that hypertrophy of the peribiliary plexus and direct anastomosis in the peripheral area of the liver are major routes of arterioportal communication in experimental rat cirrhosis [76]. Capillarization and permeability changes of sinusoids may also be related to arterioportal communications of the cirrhotic liver [76,77].…”
Section: Nontumorous Arterioportal Shunt In Liver Cirrhosismentioning
confidence: 98%
“…Hypertrophy of the peribiliary plexus and direct anastomosis in the peripheral area of the liver are the major routes of APS in experimental studies (20). Abnormal permeability of the sinusoid also has a role in the development of arterioportal communications in the cirrhotic liver (13).…”
Section: Liver Cirrhosismentioning
confidence: 99%